Structural Equation Modelling of Time Banditry under the Theory of Planned Behaviour - Kumar Dookhitram (Structural Equation Modelling of Time Banditry under the Theory of Planned Behaviour, 2024)
Companies have always tried to take action to stop workers from behaving unethically. Sadly, time banditry, which encompasses actions like coming to the workplace late or early and eating longer than required, hasn’t received enough attention from researchers. In this book, we examine the likely causes of time banditry using the "Theory of Planned Behaviour". We investigate the connections between "attitudes, subjective norms, and perceived behaviour control" and the underlying motivation for time banditry. Moreover, it is examined how the independent variables are impacted by the moderating factors of age, gender, education, and organisation size. Using convenience sample and snowball sampling, we survey 560 Mauritian employees. Techniques like structural equation modelling and moderation analysis are used to analyse the data. The results demonstrate that desire to steal time is strongly in uenced by "attitudes, subjective norms, and perceived behavioural control". Also, out of the three independent variables, attitude seems to be the best predictor. Because of this, businesses may reduce time theft by concentrating on changing employees’ views about time theft. It is evident from the results that the "Theory of Planned Behaviour" provides a solid theoretical foundation for studying time banditry. Examining the relative significance of these characteristics may reveal to employers a lot about how to minimize employee time theft. For forecasting the intention to practise banditry, the theoretical and practical implications of the "Theory of Planned Behaviour", as well as its suggestions for future study, are examined. While this book shows that attitude is the most important component in determining whether or not someone would want to engage in time banditry, other immoral behaviour may have various consequences. Further research is needed to ascertain behaviour may have various consequences. Further research is needed to ascertain behaviour.